1992
DOI: 10.1093/jnci/84.9.683
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial to Assess the Effectiveness of Breast Irradiation Following Lumpectomy and Axillary Disection for Node-Negative Breast Cancer

Abstract: Further follow-up may define an acceptable low-risk group for breast relapse. Until then, we recommend that all patients receive breast irradiation. Systemic adjuvant therapy should be considered for patients with poor nuclear grade tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
120
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(125 citation statements)
references
References 0 publications
3
120
0
2
Order By: Relevance
“…6,54 We chose the non-inferiority margin as an absolute difference of 2.5% because this seemed clinically acceptable to physicians and patients. However, during the past decade recurrence rates have substantially reduced.…”
Section: Methodsmentioning
confidence: 99%
“…6,54 We chose the non-inferiority margin as an absolute difference of 2.5% because this seemed clinically acceptable to physicians and patients. However, during the past decade recurrence rates have substantially reduced.…”
Section: Methodsmentioning
confidence: 99%
“…Early clinical data established whole breast radiation delivered over 5 to 7 weeks of daily treatment as the standard to reduce the risk of long-term toxicity (2)(3)(4)(5). In the 1990s, data became available showing that shorter courses (3-4 weeks) of treatment might be as effective without increasing toxicity (6). Owing to wide variations in the patterns of care surrounding fractionation (7,8), multiple randomized trials directly comparing hypofractionation with standard radiation were initiated, with recent long-term results confirming equivalence (9-13).…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for partial breast radiotherapy (PBRT) after breast conservation surgery for early breast cancer includes the assumption that most ipsilateral breast tumor relapses (IBTR) developing outside the index quadrant are new primary (NP) tumors that are not prevented by radiotherapy (1)(2)(3). Several phase I and II studies evaluating accelerated PBRT have reported promising early results, with few local tumor relapses, while maintaining excellent cosmetic outcomes and minimum toxicity (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%